In Vitro Test on the Effectiveness of Citrus limon and Allium sativum as Pediculicides - Susanty, Elva; Lesmana, Suri Dwi; Afandi, Dedi; Yulianto, Ragil; Andhika, Kevin Rovi (Jurnal Kedokteran Brawijaya, 2020)
Excessive usage of synthetic pediculicides, such as permethrin, lindane, and malathion, can induce resistance, environmental pollution, health problems, and even death. Efforts to prevent the side-effects of synthetic pediculicides are needed, one of which is by shifting to powerful yet safe natural pediculicides, such as Citrus limon (lemon) and Allium sativum (garlic). This study aimed to observe the effective concentration of Citrus limon and Allium sativum in vitro on the mortality of Pediculus humanus capitis (P. h. capitis). This research was an experimental laboratory study conducted in July to September 2019 in the Laboratory of Parasitology at Faculty of Medicine, University of Riau, while the making of Allium sativum extract was done at the Faculty of Mathematics and Science, University of Riau. A total of 288 samples of adult P. h. capitis was taken from children in two orphanages in Pekanbaru. Citrus limon juice and Allium sativum extract of 25%, 50%, 75%, and 100% concentrations, permethrin 1% as the positive control, and distilled water as the negative control were used in this study, and repetition was done three times. P. h. capitis mortality was observed every 10 - 120 minutes, characterized by the absence of movement of the legs and antenna. Data analysis was performed after 120 minutes with the one-way ANOVA test, LSD (=0.05), and Lethal Concentration 50 test (LC50). The one-way ANOVA test results of this study showed that statistically Citrus limon juice and Allium sativum extracts showed differences in each treatment formulation of juice on P. h. capitis mortality (Sig 0.017<0.05 and Sig 0.000<0.05) and LC50 juice of Citrus limon and Allium sativum extract by 51.999% and 72.426%. In this study, Citrus limon juice and Allium sativumÂ extract had effect as pediculicides.